Efektivitas Pembelajaran Berbasis Virtual Reality Dibandingkan Pembelajaran Tatap Muka Dalam Meningkatkan Keterampilan Klinis Mahasiswa Keperawatan: Literatur Review - Siti Zahara Nasution; Ulfah Salwani; Evi Karota Bukit; Rika Endah Nurhidayah (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2026)
Introduction : The advancement of technology in the field of education has encouraged the utilization of Virtual Reality (VR) as an innovative learning method, particularly in nursing education. Objective: This study aims to analyze the effectiveness of VR-based learning compared to conventional methods in improving the clinical skills of nursing students. Methods: This study employed a literature review approach based on PRISMA guidelines, with article searches conducted through PubMed and SINTA databases within the publication period of 2021–2026. A total of 10 journals that met the inclusion criteria were analyzed in this study. Results: The findings indicate that the use of VR significantly improves clinical skills, knowledge, self-efficacy, and professional attitudes of nursing students. In addition, VR provides a more interactive and immersive learning experience, which enhances understanding and information retention compared to conventional learning methods. When compared to face-to-face learning, VR demonstrates equivalent or even superior effectiveness in certain aspects, such as reducing stress levels and increasing learning engagement. However, the combination of VR and conventional methods (blended learning) produces the most optimal outcomes. Conclusion: VR-based learning is an effective and innovative approach in nursing education with great potential to enhance students’ clinical competencies. Therefore, the integration of VR into the nursing education curriculum is highly recommended to support more modern and high-quality learning processes.